Remote Pediatric Critical Care Telephone Consultations: Quality and Outcomes - Tijssen, Janice A.; Miller, Michael R.; Parshuram, Christopher S. (Journal of Pediatric Intensive Care, 2019)
There are no studies describing the nature and quality of telephone consultations for critically ill children despite being an important part of pediatric intensive care. We described pediatric telephone consultations to a PICU in Ontario, Canada in 2011 and 2012. Of 203 consultations, 104 patients (51.2%) were admitted to the PICU; this was associated with weekend consultations (p = 0.005) and referral hospital location (p = 0.036). Frequency of interruptions was 1 in every 3.2 (2.0, 5.7) minutes and not associated with call content. Twenty-one percent of consults had limited discussion of vital signs. Our study described our center's remote critical care consultation program and outcomes.
Keywords: pediatric critical care; remote consultation; quality